A data set for pollinator diversity and their interactions with plants in the Pacific Northwest. Issue 2 (28th December 2022) - Guzman, Laura Melissa; Kelly, Tyler; Elle, Elizabeth
Abstract: Pollinator populations have declined substantially in recent years. The resulting loss in pollination services has both ecological and economic consequences, including reductions in plant diversity and crop production and lower food security. Data sets that identify pollinators and their plant hosts are of the utmost importance for the light can shed on the main causes of pollinator declines. Here we present a data set that contains 67, 954 individual pollinator records. The data were collected across the Pacific Northwest, primarily focused in British Columbia (Canada), with 182 individual sites over 11 years, between 2005 and 2017. This data set comprises multiple studies that aimed to collect information on pollinator abundance, diversity, and their interactions with plants. Overall, the data set includes 937 morphospecies (of which 482 were identified to the species level) of pollinators across 105 families, including data for bees, wasps, butterflies, moths, and flies. We also present information on the interactions of these species, with 473 species of plants. The data set is being released for noncommercial use only. Credits should be given to this paper (i.e., proper citation).